India’s Traditional Water Conservation and Harvesting System: A solution to combating Water Scarcity - Souvik Ghosh; H. N. Verma; P. Nanda; Dinesh Chandra (Journal of Agricultural Extension Management, 2025)
Water has been harvested in India since antiquity. Evidence of this tradition can be found in many age-old ancient texts, scriptures, inscriptions, local tradition and archaeological remains. Traditional systems are the specific response to the ecology and culture in which they have evolved, they are more durable and have satisfied certain needs of local people in environment friendly manner. These systems emphasize the eco logical conservation in contrast to environmental exploitation by the modern systems. These have benefited from collective human experience since time immemorial and in that li e their bi guest strength. Traditional systems are low cost, user friendly techniques and community-based systems, which contribute to social cohesion and se lf-reliance. Often the responsibility of taking decision s and actions was left to individuals, groups and local communities working together. This encourages economic independence and optimatisation of local resources at micro-level